MicroRNA: unveiling novel mechanistic and theranostic pathways in diabetic cardiomyopathy - De, Akash; Sarkar, Arnab; Banerjee, Tanmoy; Bhowmik, Rudranil; Sar, Shuvam; Shaharyar, Md. Adil; Karmakar, Sanmoy; Ghosh, Nilanjan (Frontiers in Pharmacology, 2025)
Diabetic cardiomyopathy (DCM) is a prominent contributor to morbidity and mortality in people with diabetes worldwide. In diabetic patients, it is a chronic condition that is characterized by ventricular hypertrophy (VH), diastolic dysfunction, alteration of systolic function, and reduced ejection fraction, ultimately leading to heart failure (HF). Despite being extensively understood, the underlying causes of DCM remain obscure. Growing evidence has identified the contribution of microRNAs (miRNAs), a small non-coding RNA molecule playing a crucial part in the pathogenesis of DCM. These miRNAs have been linked with several mechanistic pathways involved in DCM, including inflammation, insulin resistance and cardiomyocyte apoptosis. miRNAs related to DCM include miR-9, 30d, 34a, 142-3p, 144, 150, 208a, etc. Thus, miRNAs present themselves as novel targets for diagnostic biomarkers and mechanistic therapeutics, which may prove to be clinically more efficient than other therapeutic approaches. This review highlights the role of miRNAs, which can act as the nodes of signalling networks that regulate the progression of DCM and also tries to decipher the complicated cross-talk between miRNAs and DCM-related signalling pathways through various protein factors modulation, which includes RyR-2, TGF-β, IGF-1R, NF-κB and Nrf-2 and also immunological regulation of cardiomyocytes. There has also been a discussion of diagnostic and therapeutic management of various miRNAs in the management of DCM with recent clinical trials on diabetes and cardiovascular disorder with miRNA candidates and concluded with the future perspective of miRNAs as new novel theranostic tools in the emerging field of diagnostic and therapeutic management.